Phytoremediation using genetically engineered plants to remove metals: a review - ÖZYİĞİT, İBRAHİM İLKER (SPRINGER HEIDELBERG, 2021)
Contamination by heavy metals including As, Cd, Co, Cu, Fe, Hg, Mn, Ni and Zn in agricultural fields is a global safety issue. Indeed, excessive accumulations of metals have detrimental effects on life by altering cell components such as lipids, proteins, enzymes and DNA. Phytoremediation appears as a solution to remove metals from contaminated sites, yet metal uptake is usually low in most common plants. Therefore, genetically engineered plants have been designed for higher efficiency of metal accumulation. Here, we review metal phytoremediation by genetically engineered plants with focus on metal uptake and transport, mechanisms involving phytochelatin and metallothionein proteins, toxicity, plant species, methods of gene transfer and gene editing.
Keywords: Transgenics; Heavy metals; Contamination; Metal transporters; Uptake and accumulation; Plants; Toxicity; Environmental friendly; PYRACANTHA-COCCINEA ROEM.; HAIRY ROOT CULTURES; SOLANUM-NIGRUM L.; HEAVY-METALS; ARABIDOPSIS-THALIANA; PHYTOCHELATIN SYNTHASE; CONTAMINATED SOIL; TRANSGENIC PLANTS; AGROBACTERIUM-TUMEFACIENS; CADMIUM ACCUMULATION